Farming occupation in the views of farmer families in rural area. (October 2019) - Widiyanti, E; Karsidi, R; Wijaya, M; Utari, P
Abstract: As main actors in food production system, farmers receive much of the world's attention due to the food crisis phenomenon happening all over the world. However, the attention to small-scale farmers tends to be neglected, especially regarding to the crisis of farmer regeneration. Thus it is interesting to understand how small-scale farmers and their families think of farming occupations. To comprehend the meanings underlying the farmer families' views on farming occupations, the researchers applied Hebert Blumer's symbolic interactionism in descriptive qualitative study using paradigm construction. The data were collected by interviews with a number of farmers and their families in Tegalmade Village, Mojolaban District, Sukoharjo Regency. The results showed that there are different views among older generation (farmers) and younger generation (farmers' children). The identified views were positive, neutral and negative. The differences in their views are caused by different interaction processes, leading to different action orientations. The young generation has positive views when interacting with their families and youth community engaged in agriculture especially in agriculture entrepreneurship. These positive views result in action orientations to work on the farming occupations. The older generation has positive views when interacting with fellow farmers, views that they want to continue to make farming as their main livelihood.